The acceptance of Islamic-based mobile banking towards cashless campus at universities in Malaysia - Andrean, Rizky (2025)
Digital payments and the cashless society have grown rapidly over the past few years and have penetrated many sectors, including the university environment through the cashless campus initiative in Malaysia. However, although this country on the top position in Islamic financial services, the use of Islamic-based mobile banking less popular than e-money. Therefore, this study examines the acceptance of Islamic-based mobile banking at universities in Malaysia using the modified UTAUT model. This study uses a quantitative approach in the form of causal research. Data collection in this study used a Google Form questionnaire with a Likert Scale. The sample in this study was 128 people consisting of students, lecturers, and staff from five universities in Northern Malaysia. Sampling was carried out using the purposive sampling method. The data analysis method is Partial Least Squares Structural Equation Modeling (PLSSEM) using SmartPLS 3 software. The results of this study indicate that performance expectancy and social influence affect behavioral intention. Meanwhile, effort expectancy, facilitating conditions, and intrinsic religiosity do not affect behavioural intention. As well as behavioral intention affects use behavior of Islamic-based mobile banking. Findings of this study provides valuable information to potential users of Islamic-based mobile banking and researchers who are interested on the area of acceptance mobile banking services.